The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2006
DOI: 10.1063/1.2185687
|View full text |Cite
|
Sign up to set email alerts
|

Statistically steady measurements of Rayleigh-Taylor mixing in a gas channel

Abstract: A novel gas channel experiment was constructed to study the development of high Atwood number Rayleigh-Taylor mixing. Two gas streams, one containing air and the other containing helium-air mixture, flow parallel to each other separated by a thin splitter plate. The streams meet at the end of a splitter plate leading to the formation of an unstable interface and of buoyancy driven mixing. This buoyancy driven mixing experiment allows for long data collection times, short transients and was statistically steady… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 82 publications
2
45
0
Order By: Relevance
“…We found excellent agreement between simulations and a miscible experiment (28) and with several immiscible experiments (29,30). See Fig.…”
Section: Verification and Validationsupporting
confidence: 61%
“…We found excellent agreement between simulations and a miscible experiment (28) and with several immiscible experiments (29,30). See Fig.…”
Section: Verification and Validationsupporting
confidence: 61%
“…The picture which emerges is that the measurement of ↵ from the fit of h(t) with t 2 is sensitive to the transient behavior which depends on the initial perturbation of the interface. It has been found that, in general, experimental measurements give a value of ↵ in the range 0.05 0.07 (Snider & Andrews 1994;Read 1984;Dimonte & Schneider 1996;Linden et al 1994;Schneider et al 1998;Banerjee & Andrews 2006) while numerical simulations report lower values around 0.03 (Cabot & Cook 2006;Dimonte et al 2004;Young et al 2001;Youngs 1991). One possible origin of this di↵erence is due to the presence of long wavelength perturbations in the experiments, while numerical simulations are usually perturbed at small scales.…”
Section: Rayleigh-taylor Experimentsmentioning
confidence: 87%
“…3 ) while a more recent setup developed by Banerjee & Andrews (2006) is capable to reach A ' 1. Another, and promising technique developed by Huang et al (2007) makes use of a strong magnetic field gradient to stabilize a paramagnetic (heavy) fluid over a diamagnetic (light) one.…”
Section: Rayleigh-taylor Experimentsmentioning
confidence: 99%
“…Although most earlier high Atwood number R-T experiments were with immiscible fluids, considerable effort now appears to be focused on miscible systems. In addition to the gas tunnel results noted previously (Banerjee & Andrews 2006), preliminary experiments using a variation on the RR (Roberts & Jacobs 2008), and high-pressure gas systems (Kucherenko et al 2003), along with novel approaches such as magnetorheological fluids (White et al 2004), are showing considerable promise, although further progress on the associated diagnostics is necessary to provide the much-needed measurements in this miscible regime.…”
Section: Discussionmentioning
confidence: 99%
“…brine/water with Sc approximately 700, and hot/cold water with Pr approximately 7. Furthermore, a new gas tunnel experiment at Texas A&M University has been developed for high Atwood number R-T studies (Banerjee & Andrews 2006). …”
Section: (D) the Water Tunnel Rayleigh-taylor Experimentsmentioning
confidence: 99%